2018
DOI: 10.1186/s41936-018-0025-7
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects induced by diclofenac, ibuprofen, and paracetamol toxicity on immunological and biochemical parameters in Swiss albino mice

Abstract: Background: Nonsteroidal anti-inflammatory drugs (NSAIDs) are generally used to reduce pain in different diseases acting as anti-inflammatory, antipyretic, and analgesic. Paracetamol is a nonprescription drug extremely used for antipyresis and analgesia. In spite of their beneficial effects, NSAIDs have been notified to be linked with some adverse effects. The present study was conducted to elucidate the comparative biochemical and immunological changes in mice treated with diclofenac (Diclo), ibuprofen (Ibu),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 45 publications
5
23
1
2
Order By: Relevance
“…Our findings reported that DS induced alteration in liver function biomarkers as it significantly elevated ALT, AST activities; significantly reduced serum total protein and albumin levels; and these findings were in accordance with the previous study reported by 28 , 29 and 30 ; who showed that liver injury resulted from NSAIDs including diclofenac sodium may be proposed to their acidic moiety or reactive metabolites that bind to host proteins inducing cellular injury; and agreed with 31 who denoted that diclofenac form significant alterations in serum protein contents by interference in protein metabolism. Furthermore, our results were in parallel with 32 who reported that increased levels of serum glutamic oxaloacetic transaminase (GOT) and serum glutamic pyruvic transaminase (GPT) indicate a marker of liver injury and damage liver cell.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings reported that DS induced alteration in liver function biomarkers as it significantly elevated ALT, AST activities; significantly reduced serum total protein and albumin levels; and these findings were in accordance with the previous study reported by 28 , 29 and 30 ; who showed that liver injury resulted from NSAIDs including diclofenac sodium may be proposed to their acidic moiety or reactive metabolites that bind to host proteins inducing cellular injury; and agreed with 31 who denoted that diclofenac form significant alterations in serum protein contents by interference in protein metabolism. Furthermore, our results were in parallel with 32 who reported that increased levels of serum glutamic oxaloacetic transaminase (GOT) and serum glutamic pyruvic transaminase (GPT) indicate a marker of liver injury and damage liver cell.…”
Section: Discussionsupporting
confidence: 93%
“…The high level of both Ur and Cr in the animals of this study was consistent with a group of studies that were carried out on albino mice [3,24] and on rats [10,22]. In contrast, the study results of [25] showed that IB caused a slight but insignificant decrease in the level of Ur and Cr in the blood of mice, contradicting the results of the current study. This difference may be attributed to the dose, method of administration, and duration of dose, and the difference in the experimental animals.…”
Section: Discussionsupporting
confidence: 86%
“…Hematological studies ( Gomaa, 2018 ) of the blood parameters were done using a Horiba Medical analyzer (model MICROS 60, USA).…”
Section: Methodsmentioning
confidence: 99%